Korelasi antara Oosit Domba yang Dikoleksi dari Rumah Pemotongan Hewan dengan Tingkat Fertilitasnya setelah Fertilisasi in vitro - Suprihatin, Teguh (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2008)
The objective of this research was to know the correlation of sheep oocytes collected from slaughterhouse and the fertility oocytes after in vitro fertilization. Data resulted from this research were quantity ofoocytes collected from slaughter house and quantity of fertilized oocytes after in vitro fertilization. Datawas analized, and resulted that coefficient correlation ( r ) was 0,4959. Conclusion of this research waspositive correlation between oocytes collected and oocytes fertilized.